Potensi Terapeutik Bunga Telang (Clitoria Ternatea L) sebagai Obat Herbal untuk Kesehatan Masyarakat Desa Parit Baru, Kabupaten Sambas: The Therapeutic Potential of Butterfly Pea Flower (Clitoria ternatea L.) as a Herbal Medicine for the Health of the Parit Baru Village Community, Sambas Regency - Denashurya, Nugra Irianta (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
The utilization of herbal medicinal plants is becoming increasingly important in raising public awareness of natural health. This Community Service activity aims to enhance the understanding of the people in Parit Baru Village, Sambas Regency, regarding the therapeutic potential of butterfly peas (Clitoria ternatea L.) as an herbal remedy. The methods used in this activity include counseling, distribution of informational media in the form of posters, and the provision of plant seedlings to the PKK women’s group. Evaluation was conducted by comparing pre-test and post-test results to measure participants' knowledge improvement. The results showed that the majority of participants experienced an increase in knowledge after attending the socialization session. Additionally, the distribution of plant seedlings and posters is expected to encourage the community to cultivate and utilize butterfly peas sustainably. Thus, this activity contributes to expanding the use of herbal medicinal plants at the community level.